Industrial Restructuring in the Budapest Agglomeration - Barta, Györgyi (Discussion Papers, 1999)
During the transition from the state-planned economy to a market economy, the Hungarian industry has fundamentally changed: Its "physical" size has radically decreased, but after a few years of a deep recession, industrial production began to increase again. The industry has undergone some thorough restructuring, its network of connections has become disaggregated, and it began to rebuild itself. Budapest’s position is exceptional within the national industrial framework. After a deeper recession and a slower recovery than the national average showed, Budapest still represents the largest industrial concentration within Hungary. It is uncertain, however, whether the main reason for the deeper industrial recession was that Budapest followed a Western city-model with its radical process of de-industrialisation, or rather more the gradual economic/industrial transformation (from the state-planned economy to a market economy) that took place at the same time. There is other open questions: Will the result be a unique Eastern European/Hungarian model, or will this region not be able to avoid the problematic path of development of the South-Asian industrialising countries? According to another scenario: Will Hungary’s and Budapest’s economy emulate the growth of handicraft-type industries similar to the so-called Italian model? This work was supported by the Research Support Scheme of the Open Society Institute (OSI/HESP, grant no. 1552/1997). Its purpose was to show the changes in the industry of the Budapest agglomeration, and to sketch probable future trends.